Case Report: Alpha-fetoprotein-producing urothelial carcinoma of the bladder - Haibing Huang; Youping Ding; Yuju Fang; Kunlin Xie; Chengyong Zhong; Haiye Fan; Xiaofeng Zou; Tianpeng Xie (Frontiers in Oncology)
Elevated serum levels of alpha-fetoprotein (AFP) are commonly associated with hepatocellular carcinoma or germ cell tumors. AFP-producing urothelial carcinoma of the bladder is very rare. We report a case of bladder urothelial carcinoma with significantly elevated AFP levels. A 60-year-old man was admitted for gross hematuria. Computed tomography urography revealed multiple large tumors of the bladder. The serum level of AFP was up to 2,329 ng/ml. No hepatic tumors or testicular tumors were detected. Although the hepatitis B surface antigen test was positive, the liver function test was normal. The patient underwent robotic-assisted laparoscopic radical cystectomy with ileal conduit urinary diversion. Postoperative pathology revealed high-grade muscle invasive bladder urothelial carcinoma and immunohistochemical staining of the tumor cells showed strong AFP positivity. After surgery, the patient’s serum AFP levels dropped sharply and decreased to normal 4 weeks after the operation. In conclusion, AFP-producing bladder urothelial carcinoma is rare, and the mechanism and pathophysiology remain unclear and require further investigation.